Acessibilidade restrita à proteção social não contributiva: um estudo sobre a invisibilidade da demanda pelo benefício de prestação continuada - Vaz, Rodrigo Isaias (2014)
The subject of this study is the demand for access to the Continuous Provision Benefit (BPC), in the specific framework of its management, regarding direction, meaning and attention. The legal and operational changes and its impacts over applicants are also part of the investigation. Regarding the Brazilian Social Security, BPC is situated in a complex place between constitutional guarantees public funding and responsibility and its practical operation. The study of the legal and institutional trajectory of BPC was drawn in order to understand the paths to the accessibility of this benefit. The analysis of the demand has a specificity: significant part of the set up of the applicants in all branches of Brazilian social security do so based in the concept of demand as an historical construction , in other words, the citizens who use the BPC, directly or forwarded by another person, do so as an alternative social protection. In this sense, the interest is not limited to the award criteria, but is also concerned with the motivations that lead the applicant to seek a support that is not determined by its binding to the pension system, but by an objective situation where someone can t afford to live on themselves. Thus, it opens a new field of analysis, that of the invisibility of those who look for the public service for protection. Regarding the historical situation of segregated and precarious conditions of the labor market in Brazil, it s possible to conclude that the applicants are characterized by informality, discontinuity and low wages, as well as permeated by gender inequalities, and this understanding is enlarged when considering working families, since protection may be required for someone who is not located in the active working age. The empirical study of the recent four-year of BPC reveals the invisibility of the profile of the applicants looking for this benefit. It required the study of the fates of the large contingent of citizens who have had their application rejected. Empirical analysis using the official data of INSS showed a significant growth on the rate of rejection of BPC, especially for women. This indicates a setback in this issue, even considering the most recent period of inclusion of disabled applicants in BPC. The restrictive criteria in the selection of applicants is also an important element, which underscores the incompleteness of social security by restricting the beneficiary to very low income limits, and not moving towards greater coverage of the disabled and elderly in their need for social protection